2021
DOI: 10.1128/mbio.01041-21
|View full text |Cite
|
Sign up to set email alerts
|

Burning the Candle at Both Ends: Have Exoribonucleases Driven Divergence of Regulatory RNA Mechanisms in Bacteria?

Abstract: Regulatory RNAs have emerged as ubiquitous gene regulators in all bacterial species studied to date. The combination of sequence-specific RNA interactions and malleable RNA structure has allowed regulatory RNA to adopt different mechanisms of gene regulation in a diversity of genetic backgrounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 72 publications
(79 reference statements)
1
8
0
Order By: Relevance
“…Therefore, one would expect the action of RNase III to trigger ftnA mRNA processing, which would provide an mRNA carrying now a 3′ end accessible for PNPase cleavage. This is in agreement with the canonical mechanism of RNA degradation found in the majority of Gram-positive bacteria, which it is initiated by either RNase Y or RNase III and followed by the action of 3′-5′ exoribonucleases such as PNPase and RNase R ( Broglia et al, 2020 ; Mediati et al, 2021 ). Our data indicated that RNase III would process the ftnA mRNA, at least in part, through its 3’UTR ( Figure 3 ).…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, one would expect the action of RNase III to trigger ftnA mRNA processing, which would provide an mRNA carrying now a 3′ end accessible for PNPase cleavage. This is in agreement with the canonical mechanism of RNA degradation found in the majority of Gram-positive bacteria, which it is initiated by either RNase Y or RNase III and followed by the action of 3′-5′ exoribonucleases such as PNPase and RNase R ( Broglia et al, 2020 ; Mediati et al, 2021 ). Our data indicated that RNase III would process the ftnA mRNA, at least in part, through its 3’UTR ( Figure 3 ).…”
Section: Discussionsupporting
confidence: 89%
“…This may be due to the presence of 5′-3′ exoribonuclease activity (RNase J1 and J2) found in Gram-positive Firmicutes , which readily degrades free 3′UTR intermediates and may represent an evolutionary barrier to the evolution of 3′UTR-derived sRNA–mRNA interactions in S. aureus (discussed in ref. 55 ). Regulatory mRNA 3′UTRs like vigR that are protected from processing at the 5′ end is likely a more widespread regulatory mechanism in S. aureus than previously appreciated.…”
Section: Discussionmentioning
confidence: 99%
“…It has been argued in a recent review (Mediati et al . 2021 ) that the smaller number of processed 3′ UTR-derived sRNAs in Gram-positive bacteria might be due to the presence of 5′ → 3′ exoribonucleolytic activity. Specifically, Gram-positive bacteria possess RNase J1, which fully degrades mRNAs from the 5′ end in one go, resulting in fewer stable intermediates for evolution to act on and limiting the development of 3′ UTR-derived sRNAs.…”
Section: Biogenesismentioning
confidence: 99%